Applications of flow cytometry in molluscan immunology: Current status and trends. Issue 94 (November 2019) - Van Nguyen, Thao; Alfaro, Andrea C.
Abstract: Flow cytometry (FCM) is routinely used in fundamental and applied research, clinical practice, and clinical trials. In the last three decades, this technique has also become a routine tool used in immunological studies of molluscs to analyse physical and chemical characteristics of haemocytes. Here, we briefly review the current implementation of FCM in the field of molluscan immunology. These applications cover a diverse range of practices from straightforward total cell counts and cell viability to characterize cell subpopulations, and further extend to analyses of DNA content, phagocytosis, oxidative stress and apoptosis. The challenges and prospects of FCM applications in immunological studies of molluscs are also discussed. Graphical abstract: Image 1 Highlights: Flow cytometry is routinely used in immunological studies of molluscan haemocytes. The use of flow cytometry has improved our understanding of molluscan immunology. Flow cytometry is an effective diagnostic tool in molluscan diseases studies. Flow cytometry can be used in combination with other techniques, such as omics.